(untitled) (Bangladesh Journal of Agriculture, 2023)
A field experiment was conducted in the Agroforestry Field Laboratory of Bangladesh Agricultural University, Mymensingh during the period from November 2016 to April 2017 to find out the effects of Sadakoroi (Albizia procera), Kalokoroi (Albizia lebbeck) and Akashmoni (Acacia auriculiformis), leaves biomass with different fertilizers dose applications on the yield and yield contributing characters of Chinese Hybrid Rice. There were 10 treatments : T1 = Sadakoroi (leaf biomass 2 kg /plot ) + 15% RFD (Recommended fertilizer dose), T2= Sadakoroi (leaf biomass 2 kg /plot )+ 30% RFD, T3 = Sadakoroi (leaf biomass 2 kg /plot )+ 45% RFD, T4 = Kalokoroi (leaf biomass 2 kg /plot) + 15% RFD, T5 = Kalokoroi (leaf biomass 2 kg /plot) + 30% RFD, T6 = Kalokoroi (leaf biomass 2 kg /plot) + 45% RFD, T7 = Akashmoni (leaf biomass 2 kg /plot) + 15% RFD, T8 = Akashmoni (leaf biomass 2 kg /plot) + 30% RFD, T9 = Akashmoni (leaf biomass 2 kg /plot) + 45% RFD and T10= Control ( 100% RFD). The boro hybrid rice var. SQR6 was used as a test crop. The experiment was conducted in a Randomized Complete Block Design (RCBD) with three replications. The result showed that green leaf biomass had a significant effect on the yield contributing characters. The panicle length varied from 21.0 to 25.5 cm. The number of leaves on hill-1 varied from 40.2-25.9. The number of effective tillers on hill-1 varied from 12.27-10.63. The highest grain yield of 8.87 t ha-1was obtained from treatment T10 followed by 8.77 tha-1 noted with T3 where Sadakoroi leaf biomass was applied. Therefore, this study suggests that the green leaf biomass of Sadakoroi and Kalokoroi can be applied to the improvement of yield and yield contributing characters of rice. Bangladesh J. Agri. 2022, 47(2): 44-52